Improving Students’ Narrative Text Writing through Narrative Endings and Story Mountain - Arnilah Arnilah; Nana Meilida Astari (Journal of English Language Teaching and Cultural Studies, 2022)
Writing skills are an essential part of communication. Good writing skills enable people to deliver their message clearly and efficiently. However, writing in a foreign language is considered the most difficult skill among other skills. Thus, the students face many challenges in writing. Hence, this study aims to investigate narrative ending and story mountain templates in improving students' ability to write narrative text. The study was conducted in SMA Islam Nurul Fikri Boarding School Serang. The participants were grade X Science 4 consists of 27 female students. The method used was classroom action research. The data was gained from observation, the writing tests, and the questionnaires given to the students. The study results based on the observation showed that the students showed more enthusiasm when the teacher applied narrative ending and story mountain template in teaching narrative text. The scores of the students' writing improved from the pre-test, which was 77, cycle 1 was 82, and cycle 2 was 86. The questionnaires revealed that the students enjoyed the writing class using narrative ending and story mountain template. They believed that both techniques were good to improve their writing skills of narrative text. Thus, it can be concluded that narrative ending and story mountain can improve students' writing of the narrative text.